Measurement-based modelling of cutting forces in micro-milling of Inconel 718. (2017) - Lu, Xiaohong; Jia, Zhenyuan; Wang, Hua; Hu, Xiaochen; Li, Guangjun; Si, Likun
Due to its superior properties, nickel-based superalloy Inconel 718 can meet the requirements of micro parts with the high strength at high temperatures which have three-dimensional geometry structure like stepped surface, deep-hole, thin wall and so on. However, Inconel 718 is difficult to cut. Now, there are few researches on the cutting forces in micro-milling of Inconel 718, and the micro-milling mechanism of nickel-based superalloy is almost blank, while the prediction and control of micro-milling forces is important to reveal the micro-milling mechanism of nickel-based superalloy, to realise processing parameter optimisation, to reduce the tool wear, etc... To predict the cutting forces during micro-milling Inconel 718 process, coated carbide tools are used to micro-milling micro groove on Inconel 718, and the orthogonal type experiments are adopted. The influences of cutting parameters on cutting forces are studied. The micro-milling forces prediction model is built based on the experimental results, which can be used to predict the cutting forces during micro-milling of Inconel 718 nickel-based superalloy. To prove the validity of the built model, the significance test and fitting degree test are conducted.